Lives of the engineers. - Smiles, Samuel, 1812-1904 (John Murray, 1877)
Samuel Smiles's Lives of the Engineers looks at locomotives and George and Robert Stephenson's lives.
Includes index.
Keywords: Locomotives -- Design and construction -- History.; Stephenson, George, -- 1781-1848.; Stephenson, Robert, -- 1803-1859.; Engineers -- Great Britain -- Biography.; elektronické knihy; electronic books